Brisingr, or, The seven promises of Eragon Shadeslayer and Saphira Bjartskular - Paolini, Christopher (New York : Alfred A. Knopf, 2008)
The further adventures of Eragon and his dragon Saphira as they continue to aid the Varden in the struggle against the evil king, Galbatorix.
"A Borzoi book"--T.p. verso.
Keywords: Fantasy; Dragons -- Fiction; Youth's writings; Fiction